2006
DOI: 10.1192/apt.12.6.416
|View full text |Cite
|
Sign up to set email alerts
|

The machine as psychotherapist: impersonal communication with a machine

Abstract: Machines will replace therapists and counsellors. This was the confident prediction made a decade ago. In this article, I discuss the inherent limitations of machines as conversationalists that have prevented the prediction from coming true. Machines can, however, be exploited to assist therapy and I consider the following digital tools: test administration; managing procedural, symptom-relieving cognitive–behavioural therapies; providing virtual environments for immersive behavioural therapies and for e-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…; see http://www. alicebot.org) have demonstrated that it is possible to train a program to recognize a particular voice and to produce spoken responses rather than text [76]. Progress has also been made in developing computer applications for detecting, labeling, and reacting to the emotional and social needs of users and for emulating empathy to create a perception of caring (e.g., [77,78]).…”
Section: Internet-operated Therapeutic Softwarementioning
confidence: 98%
See 1 more Smart Citation
“…; see http://www. alicebot.org) have demonstrated that it is possible to train a program to recognize a particular voice and to produce spoken responses rather than text [76]. Progress has also been made in developing computer applications for detecting, labeling, and reacting to the emotional and social needs of users and for emulating empathy to create a perception of caring (e.g., [77,78]).…”
Section: Internet-operated Therapeutic Softwarementioning
confidence: 98%
“…Another example of an expert system, Drinker's Check-Up, consists of integrated assessment, feedback, and decision-making modules that are sensitive to the individual's level of readiness for change, ranging from at-risk drinkers to those with alcohol dependence [81]. Such Internet-operated systems hold promise in terms of promoting psychological and behavioral change, although quantitative outcome data are still relatively scarce [76].…”
Section: Internet-operated Therapeutic Softwarementioning
confidence: 99%
“…The look also induces self-consciousness and therefore the possibility of shame (Morris, 2003). The absence of shame can be advantageous, as we shall see later (Tantam, 2006b), in the computerised administration of tests. It may also allow people to interact virtually who would be prohibited by shame or social anxiety from interacting in the flesh.…”
Section: The Lookmentioning
confidence: 98%
“…Responsiveness may be enough. Even the 1960s generation of chatterbots such as ELIZA (described in detail in the next issue: Tantam, 2006b) had users who formed emotional relationships with the computer (users do not of course differentiate between the device and the program) (Lindgaard, 2004). Our capacity to see personhood in objects in our environment and to imbue them with intentionality and emotional responsiveness towards us is considerable, as is evident in attributions of personhood to trees, the sun's disk, cars and so on.…”
Section: Presencementioning
confidence: 99%
See 1 more Smart Citation